(untitled) (Eurasian Research Bulletin, 2022)
The article provides information on the prevalence and development of gray rot disease, also known as gray mold in strawberry in Tashkent region. It has been studied and shown herein that the gray rot disease damages the fruits, pedicel, leaves and petioles of leaves of strawberry. The development and severity of the disease has been found to be caused by low air temperature, high rainfall, planting strawberries as a monoculture and a large number of weeds in the field.